In Vivo And In Vitro Studies Of Anti-Cholesterol And Anti-Carcinogenic Effects Of Ganoderma Crud Extract - Choong, Yew Keong (2003)
The in vivo and in vitro effect of a local, commercially available Ganoderma fruiting body powder (GF) and G. lucidum mycelium (GM) grown in soy waste on tumour and hypercholesterolaemic rats were studied. Administration of 1 % cholesterol diet in the cholesterol (Chol) group caused a significant (p<O.05) increase in the serum total cholesterol (TC), triglyceride (TG) and low density lipoprotein cholesterol (LDL-C) levels while reducing serum high density lipoprotein cholesterol (HDL-C) level. In the case of the Chol+GF and Chol+GM groups, the initial serum TC, TG and LDL-C levels showed a much higher levels (p<O.05) compared to the Chol group. However, the levels gradually decreased towards the end of the experiment. There was no significant difference in the lipid profiles amongst the Control, GF and GM groups. Serum alanine transferase (AL T), gamma glutamyltransferase (GGT) and creatine kinase (CK) in the Chol+GF group as well as the AL T, GGT level in the